2016
DOI: 10.5139/ijass.2016.17.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Fault Tolerant Control of Hexacopter for Actuator Faults using Time Delay Control Method

Abstract: A novel attitude tacking control method using Time Delay Control (TDC) scheme is developed to provide robust controllability of a rigid hexacopter in case of single or multiple rotor faults. When the TDC scheme is developed, the rotor faults such as the abrupt and/or incipient rotor faults are considered as model uncertainties. The kinematics, modeling of rigid dynamics of hexacopter, and design of stability and controllability augmentation system (SCAS) are addressed rigorously in this paper. In order to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The comparative simulations results showed the superiority of the proposed controller in performing the task. In another study, Lee et al [166], developed a new attitude tracking control of a hexacopter UAV subjected to a failure in one or multiple rotors subjected to external disturbances by utilizing a time delay control strategy. In this study, the superiority of the proposed strategy by adding durability and efficiency to the vehicle was illustrated when compared with the conventional PID control.…”
Section: Multi-rotor Systemsmentioning
confidence: 99%
“…The comparative simulations results showed the superiority of the proposed controller in performing the task. In another study, Lee et al [166], developed a new attitude tracking control of a hexacopter UAV subjected to a failure in one or multiple rotors subjected to external disturbances by utilizing a time delay control strategy. In this study, the superiority of the proposed strategy by adding durability and efficiency to the vehicle was illustrated when compared with the conventional PID control.…”
Section: Multi-rotor Systemsmentioning
confidence: 99%
“…In the literature, hexacopters have been a popular platform to study controllability because they seem to be robust to the failure of up to two rotors and be able to fly like quadrotors. Interestingly, however, researchers have shown that symmetric and collinear hexacopters subject to a single rotor failure are not fully controllable [14], and controllers with limited attitude controllability have been developed [11,15]. As such, carefully designed control laws can handle certain rotor failure cases that they are intended for, but it is difficult to come up with a set of control laws that can cope with all possible cases of rotor failures.…”
Section: A Related Workmentioning
confidence: 99%
“…In [22], an incremental backstepping fault-tolerant control is proposed for a hexacopter under an unknown control degradation occurring in the propulsion system. In [23], a Time Delay Control (TDC) method is presented to address single or multiple failure in the actuator. However, most of the above studies are tested and validated by simulation.…”
Section: Introductionmentioning
confidence: 99%